The New Romantics: Flaneurs and dandies of the twenty-first century. Issue 1 (1st December 2013) - Hart, Claudia; O'Brien, Nicholas
Through looking at the different ways in which alternative art practices emerged throughout the later half of the twentieth century, this article articulates how the combination of professionalized graduate education and market politics of the 1980s shaped a current generation of artists. This generation – which in actuality spans a wide range of ages, disciplines and backgrounds – creates artworks inflected with a kind of skepticism to contemporary digital technology and a criticality against the status quo akin to nineteenth-century romanticism. This article primarily examines the ways in which the Flaneur as a transgressive figure continues to influence contemporary art made within digital contexts.